Acceptability and adoption of community-based primary care for non-communicable diseases among Indonesian healthcare workers - Ardesa, Yopi Harwinanda; Pamungkasari, Eti Poncoini; Mahendradhata, Yodi; Nawi, Nawi; Probandari, Ari Natalia (Universitas Airlangga, 2026)
Introduction: Public health is confronted with the formidable problem of increased morbidity and mortality rates due to non-communicable diseases (NCDs). Primary healthcare is vital for delivering fundamental healthcare services and improving health outcomes, especially in countries with limited resources. However, studies on the evaluation and adoption of community-based primary health care are limited. This study aimed to assess the extent to which NCD management parameters were accepted and implemented by health care workers. Methods: This cross-sectional study was conducted in Klaten Regency, Indonesia. Healthcare workers involved in implementing NCD prevention and management programs, including doctors, nurses, and midwives, were recruited using convenience sampling. The independent variables included knowledge, beliefs, health worker perceptions, patient needs and resources, and readiness for implementation. Acceptability and adoption of NCD management among primary healthcare workers were the outcome variables. Data were collected using questionnaires and analyzed using multiple linear regression with a significance level of 0.05. Results: Multiple linear regression analysis indicated that readiness for implementation was the only significant predictor of acceptability (p = 0.001). Adoption was significantly predicted by patient need and resources (p = 0.003) and readiness for implementation (p = 0.001). Other variables in the model were not significant. Conclusions: This study found a moderate level of acceptability of NCD prevention and management among healthcare workers in primary care. Readiness was the only factor related to the acceptance and adoption of NCD prevention and management.